2016
DOI: 10.1038/leu.2016.300
|View full text |Cite|
|
Sign up to set email alerts
|

A randomized study of pomalidomide vs placebo in persons with myeloproliferative neoplasm-associated myelofibrosis and RBC-transfusion dependence

Abstract: RBC-transfusion dependence is common in persons with myeloproliferative neoplasm (MPN)-associated myelofibrosis. The objective of this study was to determine the rates of RBC-transfusion independence after therapy with pomalidomide vs placebo in persons with MPN-associated myelofibrosis and RBC-transfusion dependence. Two hundred and fifty-two subjects (intent-to-treat (ITT) population) including 229 subjects confirmed by central review (modified ITT population) were randomly assigned (2:1) to pomalidomide or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(29 citation statements)
references
References 31 publications
0
29
0
Order By: Relevance
“…35 A phase 1-2 study of pomalidomide reported responses in up to 36% of the patients in association with prednisone 36 ; unfortunately, a phase 3 study failed confirm these results. 37 …”
mentioning
confidence: 99%
“…35 A phase 1-2 study of pomalidomide reported responses in up to 36% of the patients in association with prednisone 36 ; unfortunately, a phase 3 study failed confirm these results. 37 …”
mentioning
confidence: 99%
“…Pomalidomide has shown similar results for anaemia improvement of 25% (+/-prednisolone) but was better tolerated (≥grade 3 neutropenia (8%) and thrombocytopenia (11%) [68]. Unfortunately, in a phase 3 study known as RESUME, pomalidomide was not superior to placebo for improving anaemia [83].…”
Section: Interferonmentioning
confidence: 95%
“…Among these, the latter three are the most recent inductees, with only pomalidomide so far receiving Food and Drug Administration approval for the treatment of advanced multiple myeloma. In a recently published phase-3 study involving patients with myelofibrosis 5 , pomalidomide was not significantly better than placebo in providing relief from red cell transfusion dependency. These results were different from those of a previously reported non-controlled study 6 , where pomalidomide displayed antianemia activity, in a subset of JAK2 -mutated patients with myelofibrosis, in the absence of marked splenomegaly or excess circulating blasts.…”
mentioning
confidence: 86%